2022
DOI: 10.3390/polysaccharides3010016
|View full text |Cite
|
Sign up to set email alerts
|

Development and Investigation of Zein and Cellulose Acetate Polymer Blends Incorporated with Garlic Essential Oil and β-Cyclodextrin for Potential Food Packaging Application

Abstract: The obtainment of new materials with distinct properties by mixing two or more polymers is a potential strategy in sustainable packaging research. In the present work, a blend of cellulose acetate (CA) and zein (60:40 wt/wt CA:zein) was manufactured by adding glycerol or tributyrin as plasticizers (30% wt/wt), and garlic essential oil (GEO), complexed (IC) or not with β-cyclodextrin (βCD), to produce active packaging. Blends plasticized with tributyrin exhibited a more homogeneous surface than those containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…As stated before, an initial screening showed that the GEO did not affect the tested bacteria equally. While the Gram-positive bacteria, such as L. innocua, had their growth impaired by the EO, none of the Gram-negative bacteria investigated appeared to be affected by it (Marques et al, 2022). In this sense, it is possible that part of the diverse microbial population in cheese was not impacted by the active films, and was able to grow normally during the storage time.…”
Section: Assaymentioning
confidence: 93%
See 4 more Smart Citations
“…As stated before, an initial screening showed that the GEO did not affect the tested bacteria equally. While the Gram-positive bacteria, such as L. innocua, had their growth impaired by the EO, none of the Gram-negative bacteria investigated appeared to be affected by it (Marques et al, 2022). In this sense, it is possible that part of the diverse microbial population in cheese was not impacted by the active films, and was able to grow normally during the storage time.…”
Section: Assaymentioning
confidence: 93%
“…Selected colonies were taken from the plate and suspended in 0.85% (wt/v) saline solution until obtaining a visual suspension density similar to 0.5 McFarland turbidity standard (approximately 10 7 CFU•mL −1 ) and diluted 1:10. Then, we proceeded with the agar dilution method, with modifications, to investigate the MIC of GEO (CLSI, 2012;Marques et al, 2022). Samples were dispersed in 10 mL of liquefied BHI agar (around 45 °C), resulting in GEO final concentrations ranging from 39.75 µg•mL −1 to 2650 µg•mL −1 , and subsequently poured into Petri dishes with a diameter of 60 mm.…”
Section: Minimal Inhibitory Concentration (Mic)mentioning
confidence: 99%
See 3 more Smart Citations